Penyuluhan Pentingnya Merawat dan Menyikat Gigi dengan Benar di SDN 1 Kemlakagede - Abdullah, Naghifari; Darwan, Darwan (Universitas Mercu Buana, 2024)
Teeth are the first part of the body to process food digestion. Good dental condition is very important for overall health, including general physical condition, the ability to chew and speak, as well as one's appearance and social relationships with others. The purpose of this research is so that students can increase their knowledge and awareness about the importance of dental health and can avoid dental caries and how to brush their teeth properly and correctly. The method used is counseling and socialization regarding how to brush teeth properly and the practice of brushing teeth directly to students in grades 4-6 SDN 1 Kemlakagede. The results of this study are that this work program can increase understanding of the importance of dental health. In addition, children also know more about how to care for and brush their teeth properly and correctly.